Rare bird documentation form for Peregrine Falcon at Mason City, 1991 - Walter, Janice L.et al (1991)
Rare bird documentation form for a Peregrine Falcon at Mason City in Cerro Gordo County, IA on February 28, 1991. Epson - sheet feed